Institutionalised whiteness, racial microaggressions and black bodies out of place in Higher Education. Issue 1 (2nd January 2019) - Joseph-Salisbury, Remi
ABSTRACT: On the morning of Friday 3 February 2017, Femi Nylander – a Black Oxford alumnus – walked through the grounds of Oxford University's Harris Manchester College. Later that morning a CCTV image of Femi was circulated to staff and students who were urged to 'maintain vigilance'. Whilst 'post-racial' ideology insists on framing such incidents as isolated aberrations bereft of wider structural and institutional context, in this article I draw upon the theoretical concepts of racial microaggressions and bodies out of place in order to disrupt this hegemonic interpretation. Adopting the Critical Race Theory (CRT) method of counter-narrative, I centralise the voices of student campaigns as sites of legitimate experiential knowledge. These campaigns reveal a web of whiteness that undergirds Higher Education. It is this web, I argue, that ensnares Femi on the day in question. Thus, Femi's experience cannot be understood in abstraction from structural white supremacy and institutionalised whiteness.